Artificial nanomotors: Fabrication, locomotion characterization, motion manipulation, and biomedical applications. Issue 2 (7th April 2022) - Wang, Liangmeng; Hao, Xiaomeng; Gao, Zhixue; Yang, Zili; Long, Yi; Luo, Ming; Guan, Jianguo
Abstract: Artificial nanomotors are nanoscale machines capable of converting surrounding other energy into mechanical motion and thus entering the tissues and cells of organisms. They hold great potential to revolutionize the diagnosis and treatment of diseases by actively targeting the lesion location, though there are many new challenges that arise with decreasing the size to nanoscale. This review summarizes and comments on the state‐of‐the‐art artificial nanomotors with advantages and limitations. It starts with the fabrication methods, including common physical vapor deposition and colloidal chemistry methods, followed by the locomotion characterization and motion manipulation. Then, the in vitro and in vivo biomedical applications are introduced in detail. The challenges and future prospects are discussed at the end. Abstract : An overview of recent developments on the fabrication, locomotion characterization, motion manipulation, and biomedical applications of nanomotors has been presented. With continued attention and innovation, it is believed that, in the future, nanomotors will innovate biomedical applications.